Optical polarization observations of NGC 6231: Evidence for a past supernova fingerprint - Feinstein Baigorri, Carlos (2003)
We present the first linear multicolor polarization observations for a sample of 35 stars in the direction of the Galactic cluster NGC 6231. We have found a complex pattern in the angles of the polarimetric vectors. Near the core of this cluster the structure shows a semicircular pattern that we have interpreted as a reorientation of the dust particles showing the morphology of the magnetic field. We propose that a supernova event occurred some time ago and produced a shock on the local ISM. We discuss in this paper independent confirmations of this event, both from the studies on the diffuse interstellar absorptions and the results of the pre-main-sequence stars. We also show that a supernova is supported by the evolutionary status of the cluster.